The Integration of Pediatric Emergency Simulation in an Undergraduate Curriculum - Manal A. Halwani, (Journal of King Abdulaziz University: Medical Sciences, 2020)
integration of paediatric emergency simulation in undergraduate curriculum. A cross-sectional study was carried out at the Clinical Skills and Simulation Centre at King Abdulaziz University in Jeddah, Saudi Arabia during the academic year 2015-2019. The questionnaire was designed to evaluate students’ simulation experience before integration in the academic year 2015-2016 curriculum and after integration in paediatric course in 2017- 2018 and paediatric emergency course in 2019. A qualitative section was also included in the questionnaire for students’ comments. The total valid responses to the questionnaire were 549. Number (Percentage) of responses to the fi rst and second questionnaire were 32.7% and 67.3%, respectively). A statistical signifi cant diff erence was found in students’ perceptions of their simulation experiences between the questionnaire groups (P < 0.001), viz., before integration of simulation-based education, and after integration for both courses. The integration of simulation into the curriculum received favourable ratings, as measured by students’ perceptions of the learning experience. The internal consistency of the fi rst questionnaire was very good (α = 0.845) and was excellent (α = 0.972) for the second.